Taţwîr Wasîlah Tadrîs Al-Mufradât Bi Canva Li As-Shaf As-Sâbi’ Fî Al-Madrasah Al-Tsânawiyah Al-Hukûmiyah - Hasanah Izzaty (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2021)
Media are devices and tools used by a teacher to improve the teaching and learning process. Canva is an online graphic design website and application that makes it easy for users to create attractive images or graphics. This research is a development research with 4D model which consists of four steps, namely; definition, design, development, and deployment. However, the researcher limits the development procedure in terms of assessing media based on experts in terms of media and teaching materials. The development procedure in this research is; the development needs analysis stage, namely the analysis of the needs of Arabic teachers and students, the 2013 curriculum, and student books. The results of the data obtained show a rating of "Excellent" in the sense that the development of this media is very much needed. Then the planning stage; starting from collecting vocabulary, downloading Canva, creating a Canva account, then submitting teaching materials to the Canva page. After you have finished creating your Canva learning media product, proceed to the development stage, namely; with expert verification, product modification and final production. The media validation results show a "Very Good" rating, which means that Canva can be used in vocabulary learning for seventh graders in State High Schools